The experience of ancient Egypt - David, A. Rosalie (Ann Rosalie) (Experience of archaeology., 2000)
This book provides a comprehensive portrait of what we know about ancient Egypt today, examining in detail issues of religion, of beliefs and practices surrounding death, of everyday life and of literature.